Development community participation questionnaire to understand the factors that influence Covid-19 booster vaccination in Yogyakarta, Indonesia - Kuncoro Kuncoro; Ezi Emira; Eka Kurnia Sari; Nurul Kodriati; Sitti Nur Djannah (Jurnal Cakrawala Promkes, 2023)
Covid-19 has resulted in fatalities and property losses not just in Indonesia but across the globe. Indonesia has the second-highest number of Covid-19 cases in Southeast Asia. The government has attempted several efforts, including vaccination. The enormous impact of vaccination in preventing illness, disability, and even death from diseases that can be prevented by immunization has been documented throughout history. The goal of COVID-19 immunization is to prevent the spread of COVID-19, lessen COVID-19-related morbidity and mortality, create community-wide herd immunity, and protect individuals against COVID-19. Achievement of booster vaccinations in the work area of PHC Playen 1 is only 41%; there is a gap of 9% from the target. This research aims to create assessment tools to identify the variables that may affect community involvement in the COVID-19 booster immunization program. Making a legitimate and trustworthy questionnaire to determine the factors that influence community participation in booster vaccinations in the working area of UPT PHC Playen 1 is the research's unique goal. This study uses a cross-sectional research design and is descriptive. The research was conducted in October 2022. Questionnaires were distributed to pre-selected respondents using the purposive random sampling method. Testing the validity and reliability of the questionnaire requires a sample of 30 people from the PHC Playen 1's working area to make up the sample. The questionnaire had five sections: the respondent's sociodemographic, their willingness, their level of knowledge, the regulation of booster vaccinations, and the community's access to booster immunization services. The data were validated and verified employing Cronbach Alpha score of 0.861 and a Pearson correlation test result showing that each statement item was valid and trustworthy by having a correlation value of higher than 0.361. Thus, this questionnaire could be employed in other related research.